2012
DOI: 10.3109/03009742.2011.623137
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of rheumatoid arthritis synovial lining regions by cDNA microarray combined with laser microdissection: up-regulation of inflammation-associated STAT1, IRF1, CXCL9, CXCL10, and CCL5

Abstract: ObjectivesThe main histological change in rheumatoid arthritis (RA) is the villous proliferation of synovial lining cells, an important source of cytokines and chemokines, which are associated with inflammation. The aim of this study was to evaluate gene expression in the microdissected synovial lining cells of RA patients, using those of osteoarthritis (OA) patients as the control.MethodsSamples were obtained during total joint replacement from 11 RA and five OA patients. Total RNA from the synovial lining ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 50 publications
6
52
0
Order By: Relevance
“…Indeed, there was significant elevation of concentrations of serum pro-inflammatory cytokines (IL-1β, IL-6, IL-18, IL-17, IL-27) [2,33,34], and chemokines (CXCL8, CXCL9, CXCL10, and CCL5) [35]. In addition, anomalous activation of various signaling axes including various MAPK, AKT, NFkappaB, Bcl-2 family members, and JAK/STAT has been suggested to affect multiple molecular processes in RA [36], and these signaling pathways may involve in the aberrant production of sCTLA-4, sCD28 and sCD80 in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there was significant elevation of concentrations of serum pro-inflammatory cytokines (IL-1β, IL-6, IL-18, IL-17, IL-27) [2,33,34], and chemokines (CXCL8, CXCL9, CXCL10, and CCL5) [35]. In addition, anomalous activation of various signaling axes including various MAPK, AKT, NFkappaB, Bcl-2 family members, and JAK/STAT has been suggested to affect multiple molecular processes in RA [36], and these signaling pathways may involve in the aberrant production of sCTLA-4, sCD28 and sCD80 in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…RA patients having low levels of TNF-α expression, who as well containing the expression of other genes at the degree of strong subjects, must be stratified into a diverse subset needing particular treatment that may include targets except pro-inflammatory cytokine signaling paths. Yoshida et al [20] assessed gene expression in the micro-dissected synovial lining cells of RA patients, by means of those of Osteoarthritis (OA) patients as the control. The molecular activity of RA was reliable with its medical as well as histological activity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De Hooge et al reported that zymosan-induced arthritis in STAT1-deficient mice is associated with increased joint inflammation and formation of granuloma (74). Yoshida et al using microarray analysis in 16 patients (11 patients with RA and 9 with osteoarthritis (OA) suggested that the expression levels of STAT1 were significantly higher in RA synovium compared to OA (86) reported that arthritis severity in mice appeared to be regulated by IL-4 through a STAT6 dependent mechanism (93). In IL-4 or STAT6 deficient mice, they observed a more severe and progressive arthritis suggesting IL-4 mediates anti-inflammatory reaction through STAT6 (93).…”
Section: N Rheumatoid Arthritis and Signal Transducer And Activatorsmentioning
confidence: 99%